The Additions Of Telang Flower Extraxtc Towards Quality Of Goat Milk Ice Cream - Riyansa, Ledya; Syarif, Wirnelis (Universitas Negeri Padang, 2023)
The background of this research is that the telang flower extract is not optimal for use in food processing. Telang flower extract can be an alternative as an additive in making ice cream. This study aims to analyze the effect of adding telang flower extract with a treatment of 0%, 20%, 30%, 40%. Regarding the quality of color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design method. Three repetitions were carried out with 3 expert panelists in the Culinary Workshop of the Department of IKK, FPP, UNP. The dependent variable (Y) is the quality of the ice cream. The instrument used was an organoleptic test through a level test, using ANOVA statistics and if it was significantly different it was continued with Duncan's test. The results showed that there was a significant effect on color quality. Meanwhile, there is no significant difference in aroma, taste and soft texture. It can be concluded that the best percentage is found in the addition of 40% telang flower extract to the quality of goat's milk ice cream.